Genome-Wide Identification and Analysis of Small Nucleolar RNAs and Their Roles in Regulating Latex Regeneration in the Rubber Tree (Hevea brasiliensis) - Chen, Xiang; Deng, Zhi; Yu, Dingwei; Zhang, Xiaofei; An, Zewei; Wu, Wenguan; Liang, Qun; Huang, Xiao; Huang, Huasun; Cheng, Han (Frontiers in Plant Science, 2021)
Small nucleolar RNAs (snoRNAs) are a class of conserved nuclear RNAs that play important roles in the modification of ribosomal RNAs (rRNAs) in plants. In the rubber trees, rRNAs are run off with the latex flow during tapping and need to be regenerated for the maintaining the functions of the laticifer cells. SnoRNAs are expected to play essential roles in the rRNA regeneration. However, snoRNAs are largely un-characterized in rubber tree. In this study, nuclear RNA sequencing was used to identify snoRNAs globally and their roles in latex regeneration was investigated. Totally 3,626 snoRNAs were identified by computational prediction with the nuclear RNA-seq data. Among these snoRNAs, fifty were shown to be highly expressed in latex, in which 31 were further validated to be latex abundant by RT-PCR. The correlation between snoRNA expression and adjusted total solid content (TSC/C) identified 13 positively yield correlated snoRNA. For better studying the latex regeneration in rubber tree, a novel insulated tapping system was developed, which only measure the latex regenerated in dedicated laticifers. Using this system, a laticifer abundant snoRNA, HbsnoR28, was found to be highly correlated with latex regeneration. This is the first report that globally identify snoRNAs that might be involved in latex regeneration regulation, and provide new clues for unravelling the latex regeneration regulation mechanisms.